Is There an Indian Precariat? Evidence from the Auto Manufacturing Industry. Issue 2 (15th March 2022) - Barnes, Tom
ABSTRACT: Guy Standing's precariat thesis, which suggests that precarious workers have distinctive class interests, has resonance in India where the overwhelming majority of workers lack adequate social protection. Among many criticisms, researchers have responded that this thesis ignores the historical experience of workers in poor countries and erroneously frames precarity as the province of a separate social class. As part of this debate, Erik Olin Wright argued that precarious workers were better understood as a potential fraction of the working class whose interests sometimes complemented and sometimes conflicted with the interests of other workers depending upon the regulatory scale and political terrain of struggle. Using an ethnography-based case study of automotive manufacturing in India's National Capital Region, this article considers which of these frameworks – Standing's or Wright's – is better able to address the dynamic of contemporary struggle in a local labour control regime which has displaced an established core of "regular workers" with a surplus population of precarious "contract workers."